2010
DOI: 10.1007/s11274-010-0545-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory and anti-tumor activity of a water-soluble polysaccharide from Phellinus baumii mycelia

Abstract: A 17-kDa water-soluble polysaccharide (PB) was isolated and purified from Phellinus baumii using the DEAE-Sephadex A-50 and LPLC-Sephadex G-75 methods. Exposure of RAW264.7 macrophages to PB resulted in a significant increase of the cellular proliferation rate, nitric oxide production and expression levels of the IL-1b, IL-18, IL-6, IL-12p35 and IL-12p40 genes. An MTT assay indicated that PB markedly suppressed the proliferation of HepG 2 human liver cancer cells in a dose-dependent manner. Cell cycle analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…From previous literature, CS-hEPS inhibition rate was better than that obtained by polysaccharides from Cordyceps militaris (57.11% at 8 mg/mL and 72 h of incubation) [59]. e inhibition rate is also close to that obtained by polysaccharide from Phellinus baumii which suppresses the HepG-2 cells proliferation by 61.2% at 400 μg/mL and 48 h of treatment period [60]. It is quite clear from our findings that CS-hEPS are more effective against myelogenous leukemia K562 cells, with similar antiproliferative effect of 5-FU, but with doses 8 to 12 times higher than that of 5-FU.…”
Section: Discussionsupporting
confidence: 62%
“…From previous literature, CS-hEPS inhibition rate was better than that obtained by polysaccharides from Cordyceps militaris (57.11% at 8 mg/mL and 72 h of incubation) [59]. e inhibition rate is also close to that obtained by polysaccharide from Phellinus baumii which suppresses the HepG-2 cells proliferation by 61.2% at 400 μg/mL and 48 h of treatment period [60]. It is quite clear from our findings that CS-hEPS are more effective against myelogenous leukemia K562 cells, with similar antiproliferative effect of 5-FU, but with doses 8 to 12 times higher than that of 5-FU.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, CSPS-1 was supposed to have a backbone of (1 → 6)-linked α-D-Glc and α-D-Gal, and contain minor β-(1 → 4)-D-Xyl and β-(1 → 4)-D-Man residues located in the side chains with a trace amount of α-(1 → 3)-L-Rha residue. Previous studies showed that polysaccharides display antitumor activity not only by stimulating proliferation of T lymphocytes, cytokine secretion, and immune function in vivo [26,27], but also have direct effects on tumor cells in vitro [28][29][30]. In the present study, the antiproliferative effect of CSPS-1 on S-180 cells was exerted through an apoptotic pathway in vitro.…”
supporting
confidence: 50%
“…This structurally diverse class of macromolecules can profoundly affect biological activities in macrophages. On the basis of the results above, we found that PSP has the same biological activity as other polysaccharides (Phellinus baumii mycelia, pine-mushroom, and Angelan), [29][30][31] and probably regulates NF-kB/MAPKs with the same mechanism (TLR4 and/or TLR2 pathway). Much more research is required to elucidate the relationship of the structure and activity of puried polysaccharides and their role in the immune response.…”
Section: Discussionmentioning
confidence: 98%